Social entrepreneurship as an agent in the intermediation of social innovation in companies - Oliveira, Nathan Pedroni de; Figueiró, Paola Schmitt; Souza, Ana Clara Aparecida Alves de (Contextus - Revista Contemporânea de Economia e Gestão, 2021)
Organizations play a fundamental role in mitigating social inequality, with emphasis on social enterprises. Thus, the objective is to analyze how a social enterprise acts as an intermediator to promote social innovations in companies. A case study was held in a local social enterprise located in the city of Porto Alegre, Brazil, and which develops projects of social impact for other organizations. The data stems from participant observation, interviews, and access to secondary data. The results indicate that social innovation is generated from the interaction between client companies and the final benefited public, through the intermediation promoted by the analyzed company, when conducting the process of creating and implementing social projects.